Catalytic hydroconversion processes for upcycling plastic waste to fuels and chemicals. Issue 5 (5th January 2023) - Wei, Junde; Liu, Jieyi; Zeng, Weihao; Dong, Zichen; Song, Jingkuo; Liu, Sibao; Liu, Guozhu
Abstract : This review provides an overview of catalytic hydroconversion processes including hydrocracking, hydrogenolysis and hydrodeoxygenation for upcycling of plastic wastes into fuels and valuable chemicals. Abstract : Plastic waste represents an environmental threat and a huge economic loss. Catalytic hydroconversion of plastic wastes can enable valorization of plastic wastes to diverse value-added products at high selectivity under mild reaction conditions, attracting significant attention. In this review, we focus on the recent advances in the catalytic hydroconversion processes for upcycling plastics wastes to fuels and valuable chemicals. The hydrocracking and hydrogenolysis of polyolefins as well as the hydrogenolysis and hydrodeoxygenation of heteroatom-containing plastics are summarized and exemplified. Besides, hydroconversion of plastic wastes by using in situ generated hydrogen is also described. We emphasize the recent progress in catalyst design and its performance. Further, we systematically discuss the functions of typical catalysts and the reaction mechanisms to gain insight into the hydroconversion of plastic wastes. In addition, the effect of some key factors, including macro- and microstructure of plastics, additives, and reaction conditions, on the catalytic performance is demonstrated as well. Given the existing contributions, a perspective is provided to address the challenges and opportunities in the field and to evaluate some potential solutions and avenues for future research. We hope that this review will inspire future research on the rational exploration of optimal catalysts with hydroconversion processes for chemical upcycling of plastic wastes to build a circular plastic economy.